World Bank Research Digest, Vol. 5(2) - World Bank (Washington, DC, 2014)
In this issue: growth and development at the center of the G-20 agenda; food price inflation in South Asia: crisis revisited? How fast can Egypt grow? Sustainable energy policy and nuclear power; access to HIV/AIDS treatment and risky sexual behaviors; the investment climate when firms have climate control; and bank capital: lessons from the financial crisis.